Surface composition of MAPb(I x Br 1−x ) 3 (0 ≤ x ≤ 1) organic-inorganic mixed-halide perovskites - Atip Pengpad (2019)
© 2019 Organic-inorganic halide perovskites have been used as light absorbers in photovoltaic cells. The energy band gap of these perovskites can be tuned by mixing various halides at different concentrations. In this work, mixed iodide-bromide perovskite films at various concentrations were deposited on fluorine-doped tin oxide glass substrates via a spin coating technique. The films were characterized using X-ray diffraction (XRD), ultraviolet-visible spectroscopy and synchrotron-radiation photoemission spectroscopy. The XRD results suggest that the lattice spacing decreased with increasing bromide concentration, which also relates to an increase in the energy band gap. The mixed halide films showed less crystallinity than that of pure halide films. The photoemission results showed that the iodide concentration at the surface was higher than expected. This could have been due to the higher solubility of iodide perovskite in the dimethylformamide solvent than that of bromide perovskite. These results suggest that the energy levels at the surface of the films can be different from those of the bulk material.